Early Skin-to-Skin Contact in Preterm Infants: Is It Safe? An Italian Experience - Luca Bedetti; Licia Lugli; Natascia Bertoncelli; Eugenio Spaggiari; Elisabetta Garetti; Laura Lucaccioni; Federica Cipolli; Alberto Berardi (MDPI AG, 2023)
Background: Skin-to-skin contact (SSC) is one of the four components of kangaroo care (KC) and is also a valued alternative to incubators in low-income countries. SSC has also become a standard of care in high-income countries because of its short- and long-term benefits and its positive effect on infant growth and neurodevelopmental outcome. However, barriers in the implementation of SSC, especially with preterm infants, are common in NICUs because parents and health care professionals can perceive it as potentially risky for the clinical stability of preterm infants. Previous studies have assessed safety before and during SSC by monitoring vital parameters during short-time intervals. Aims: To demonstrate the safety of early SSC in preterm infants during at least 90 min intervals. Design: Prospective observational monocentric study. Methods: Preterm infants born between June 2018 and June 2020 with a gestational age of ≤33 weeks and a birth weight of <2000 g were monitored while performing an SSC session during the first three weeks of life. Infants with necrotizing enterocolitis, sepsis, and congenital malformations on mechanical ventilation or with more than five apneas in the hour before SSC were excluded. Continuous oxygen saturation (SaO2), heart rate (HR), and respiratory rate (RR) were registered during an SSC session and in the hour before. The minimum duration of an SSC session was 90 min. Information regarding postmenstrual age (PMA), body weight, respiratory support, presence of a central venous catheter and the onset of sepsis within 72 h after a session was collected. Two physicians, blinded to infant conditions and the period of analysis (before or during SSC), evaluated desaturation episodes (SaO2 < 85%, >15 s), bradycardia (HR < 100, >15 s) and apneas (pause in breathing > 20 s associated with desaturation and/or bradycardia). A Wilcoxon rank sum test was used for the statistical analysis. Results: In total, 83 episodes of SSC were analyzed for a total of 38 infants. The mean gestational age at birth was 29 weeks (range 23-33 weeks). Median PMA, days of life, and body weight at SSC were 31 weeks (range 25-34 weeks), 10 days (range 1-20 days), and 1131 g (range 631-2206 g), respectively. We found that 77% of infants were on respiratory support and 47% of them had a central venous catheter (umbilical or peripherally inserted central catheter) during SSC. The total duration of desaturation, bradycardia, and the number of apneas were not statistically different during the SSC session and the hour before. No catheter dislocation or ruptures were reported. Conclusions: These findings highlighted the safety of early SSC in preterm infants and the possibility of performing it in an intensive care setting in the first weeks of life. In addition, these findings should reassure health care professionals offering this practice as a standard of care. SSC plays a key role in the care of preterm infants due to its short- and long-term positive benefits, and it deserves to be increasingly offered to infants and their parents.